2009
DOI: 10.1186/1687-9856-2009-578610
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hyperprolactinemia and Bilateral Galactocele in a Male Infant

Abstract: Galactocele is a benign breast lesion, usually occurring in nursing women. This lesion is a rare cause of breast enlargement in children. In this paper we describe the case of an infant with hyperprolactinemia (which persisted throughout 15 years of clinical observation) and bilateral galactocele. We speculate that a congenital midline defect in our patient might have impaired the normal dopaminergic inhibitory tone on pituitary lactotroph cells, thus leading to an increased prolactin secretion by the pituitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Simple excision through the intra-areolar incision was curative in all reported cases 2,4,[8][9][10][11] , as was in this patient. The needle aspiration of cyst fluid may eliminate the need for the surgery but there are only three such cases reported in the literature 4,5 .…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Simple excision through the intra-areolar incision was curative in all reported cases 2,4,[8][9][10][11] , as was in this patient. The needle aspiration of cyst fluid may eliminate the need for the surgery but there are only three such cases reported in the literature 4,5 .…”
Section: Discussionmentioning
confidence: 49%
“…However, one previously reported 28-month-old boy with unilateral galactocele had persistent hyperprolactinemia 8 and another 18-month-old infant with bilateral breast involvement had elevated insulin-like growth factor-1 because of growth hormone treatment of congenital hypopituitarism 9 . In only 3 reported cases, all with unilateral galactocele, isolated congenital malformation was described: renal dysplasia 1 , ventricular septal defect 10 , and cleft lip 11 .…”
Section: Discussionmentioning
confidence: 98%
“…It has been proposed that it may be associated with stimulation by prolactin, ductal obstruction or the presence of secretory breast epithelium 3–5. It has been reported only in a single male infant with persistent hyperprolactinaemia and bilateral galactoceles 3. Dopamine receptor agonists (cabergoline or bromocriptine) may decrease serum prolactin levels, however hyperprolactinaemia was not present here.…”
Section: Answers To the Questions On Page XXmentioning
confidence: 57%
“…It is usually unilateral although bilateral cases have been reported. The aetiology is unknown but it has been suggested that it may be associated with previous or present stimulation by prolactin, some form of ductal obstruction or the presence of secretary breast epithelium 3 4. Previous case reports have included a male infant with persistent hyperprolactinaemia and another with panhypopituitarism 3 5.…”
Section: Resultsmentioning
confidence: 99%